The Effect of Fear of COVID-19 on Green Purchase Behavior in Pakistan: A Multi-Group Analysis Between Infected and Non-infected - Sajid, Kubra S.; Hussain, Shahbaz; Hussain, Rai I.; Mustafa, Bakhtawar (Frontiers in Psychology, 2022)
The covid-19 pandemic and its effects on an individual’s life have altered consumer behavior. In the context of purchase and consumption, a shift from conventional to green purchase has been noticed. Although the factors underlying this shift were relatively unexplored, the study aimed to identify the factors that influenced a significant role in the green purchases during the outbreak and the relationship of these factors with GPB. Subsequently, this study investigates and interprets the role of fear of covid-19, psychological distress, and mortality salience in predicting consumer’s green purchase behavior. This research adopted a quantitative methodology using data collected from 432 respondents in various cities across Pakistan. Smart-PLS 3 was used to evaluate the measurement model, structural model, and multi-group analysis. Despite having the negative psychological and physical impact of the pandemic, a significant proportion of customers have switched to healthier and sustainable products. This research revealed that the fear of covid-19, psychological distress, and mortality salience play a substantial role in adopting green purchase behavior. All the direct relationships were positive and significant. Also, mortality salience and psychological distress partially mediate the effect of fear of covid-19 on green purchase behavior. Furthermore, the multi-group analysis revealed that the infected respondents were interested in purchasing green products than uninfected respondents due to their FCV; conversely, the psychological distress and mortality salience were higher in uninfected individuals than infected ones. However, there is a vast literature on green purchase behavior, but little has investigated the cumulative impact of fear of covid-19, psychological distress, and mortality salience on green purchase behavior.